2018
DOI: 10.35808/ijeba/179
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility on SKI KEHATI Index Corporate Performance: A Case Study

Abstract: Many companies are now increasingly aware of the importance of implementing Corporate Social Responsibility (CSR) as part of their business strategy and as the embodiment of the company's concern to society. This study specifically examines the SRI-KEHATI Index which is a new index that specifically includes issuers that have excellent performance in encouraging sustainable businesses, as well as having awareness of the environment, social and good corporate governance using an analysis technique that is regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In addition, these firms are also considered to have a good corporate governance. The SRI KEHATI Index is an index that describes firms that do not only benefit economically but also pay attention to the environmental preservation around them (Lakaba & Robiyanto, 2018;Utomo, Wahyudi, Muharam, & Taolin, 2018;Wahyudi, Pangestuti, Laksana, Hersugondo, & Robiyanto, 2018). The SRI KEHATI Index was formed to spread the information widely to the wider community, so that they would recognize the characteristics of firms that have environmental concerns, community involvement, human resources, corporate governance, human rights, and acceptable business ethics on international level (Zulkafli, Ahmad, & M., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these firms are also considered to have a good corporate governance. The SRI KEHATI Index is an index that describes firms that do not only benefit economically but also pay attention to the environmental preservation around them (Lakaba & Robiyanto, 2018;Utomo, Wahyudi, Muharam, & Taolin, 2018;Wahyudi, Pangestuti, Laksana, Hersugondo, & Robiyanto, 2018). The SRI KEHATI Index was formed to spread the information widely to the wider community, so that they would recognize the characteristics of firms that have environmental concerns, community involvement, human resources, corporate governance, human rights, and acceptable business ethics on international level (Zulkafli, Ahmad, & M., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship has been found to hold for the PSEi, as the authors have discovered a significant short and long-run relationship between the exchange rate and the PSEi. Similarly, Wahyudi et al (2017) found that the exchange rate has a positive and significant impact on the price levels the market index in Malaysia and Thailand. They used the TARCH model to examine the relationship between the PSEi and the exchange rate, with the results indicating that the exchange rate significantly negatively affects the price levels of the PSEi.…”
Section: Exchange Ratementioning
confidence: 87%
“…However, to the best of the authors' knowledge, there is limited research dedicated to studying the PSE, let alone the macroeconomic determinants of the PSE Index (PSEi). The existing literature indicates that the Philippine stock market is sensitive to macroeconomic factors such as changes in the gross domestic product (GDP), money supply, income levels, unemployment, inflation, exchange rates, and other macroeconomic variables (Wahyudi et al, 2017;Ho & Odhiambo, 2018;Endres, 2020). However, there is still a significant need for further research on the macroeconomic determinants of the PSEi and the relationship between the PSEi and macroeconomic variables.…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%
“…Selain itu, perusahaan dengan pertumbuhan yang besar menghasilkan lebih banyak keuntungan sehingga pemakaian hutang memberikan manfaat bagi perusahaan, yaitu adanya penghematan pajak (Lisboa, 2019). Handriani & Robiyanto (2018) dan Wahyudi et al (2018) dalam penelitiannya, mendapati adanya hubungan yang relevan antara pertumbuhan bisnis dan investasi dalam studi empiris mereka. Temuan penelitian sebelumnya membuktikan adanya hubungan positif antara pertumbuhan perusahaan dengan kebijakan hutang (Sutomo et al, 2019) Penelitian ini menggunakan penelitian kausal komparatif untuk menganalisa hubungan sebab akibat pada dua variabel atau lebih.…”
Section: C) Hubunganunclassified